Spatiotemporal dynamics of emerging pathogens in questing Ixodes ricinus - Coipan, Elena C.; Jahfari, Setareh; Fonville, Manoj; Maassen, Catharina; van der Giessen, Joke; Takken, Willem; Takumi, Katsuhisa; Sprong, Hein (Frontiers in Cellular and Infection Microbiology, 2013)
Ixodes ricinus transmits Borrelia burgdorferi sensu lato, the etiological agent of Lyme disease. Previous studies have also detected Rickettsia helvetica, Anaplasma phagocytophilum, Neoehrlichia mikurensis, and several Babesia species in questing ticks in The Netherlands. In this study, we assessed the acarological risk of exposure to several tick-borne pathogens (TBPs), in The Netherlands. Questing ticks were collected monthly between 2006 and 2010 at 21 sites and between 2000 and 2009 at one other site. Nymphs and adults were analysed individually for the presence of TBPs using an array-approach. Collated data of this and previous studies were used to generate, for each pathogen, a presence/absence map and to further analyse their spatiotemporal variation. R. helvetica (31.1%) and B. burgdorferi sensu lato (11.8%) had the highest overall prevalence and were detected in all areas. N. mikurensis (5.6%), A. phagocytophilum (0.8%), and Babesia spp. (1.7%) were detected in most, but not all areas. The prevalences of pathogens varied among the study areas from 0 to 64%, while the density of questing ticks varied from 1 to 179/100 m2. Overall, 37% of the ticks were infected with at least one pathogen and 6.3% with more than one pathogen. One-third of the Borrelia-positive ticks were infected with at least one other pathogen. Coinfection of B. afzelii with N. mikurensis and with Babesia spp. occurred significantly more often than single infections, indicating the existence of mutual reservoir hosts. Alternatively, coinfection of R. helvetica with either B. afzelii or N. mikurensis occurred significantly less frequent. The diversity of TBPs detected in I. ricinus in this study and the frequency of their coinfections with B. burgdorferi s.l., underline the need to consider them when evaluating the risks of infection and subsequently the risk of disease following a tick bite.